A Mathematical Programming Model for Test Construction and Scoring - Feuerman, Martin; Weiss, Harvey (Management Science, 1973)
A method is presented for test construction and scoring which utilizes the knapsack model of mathematical programming. The method applies to examinations of the type in which a choice exists in the number of questions the examinee is required to answer. The method has been utilized with respect to a Mathematics examination and computer generated results of this test are provided.